Integer conformal dimensions for type IIa flux vacua - Apers, F; Conlon, J; Ning, S; Revello, F (American Physical Society, 2022)
We give a concise argument that supersymmetric anti–de Sitter type IIA DeWolfe-Giryavets-Kachru-Taylor flux vacua on general Calabi-Yau’s have, interpreted holographically, integer conformal dimensions for low-lying scalar primaries in the dual conformal field theory. These integers are independent of any compactification details, such as the background fluxes or triple intersection numbers of the compact manifold. For the Kähler moduli and dilaton, there is one operator with Δ=10 and h1,1− operators with Δ=6, whereas the corresponding axions have Δ=11 and Δ=5. For the complex structure moduli, the h2,1 saxions have Δ=2, and the axions Δ=3. We give a tentative discussion of the origin of these integers and effects that would modify these results.